Pengaruh stretching exercise terhadap kebosanan dan kelelahan belajar pada siswa di SMP Muhammadiyah Kedungbanteng - Jorinda Salsabila; Vivi Leona Amelia (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: Identifying the effect of stretching exercise on learning boredom and exhaustion in SMP Muhammadiyah Kedungbanteng.Method: This was a quantitative research used a quasi-experimental design. The research sample was taken through total sampling, in which there were 47 respondents who were in accordance with the implemented inclusion and exclusion criteria. The research instruments used a questionnaire sheet and analyzed with the t-test sample independent test.Results: In the intervention group most of the students aged 14 years old (36.2%), the total of grade 9 was mostly (55.3%), and most of them were female (80.9%). In the control group most of the students were 13 years old (42.6%), the total of grade 7 were mostly (51.1%), and most of them were female (66.0%). The students have average boredom of 53.17± 8,310 sd and the average exhaustion of 30.57±5,428 sd. The result of the t-test sample independent test for boredom obtains a p-value of 0,0001 and the result of the t-test sample independent test for exhaustion obtains a p-value of 0,0001. Conclusion: There was an effect of stretching exercise on the learning boredom and exhaustion in SMP Muhammadiyah Kedungbanteng.